2008
DOI: 10.1177/0741932508324399
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Responsibilities, and Training Needs of Paraprofessionals in Elementary and Secondary Schools

Abstract: The authors queried 313 paraprofessionals working in 77 elementary, middle, and high schools about (a) the contexts within which they support students with disabilities, (b) their knowledge about core competencies in educating these students, (c) the job-related tasks they perform most frequently, (d) their perceived ability to perform these tasks effectively, and (e) their need for further training across these knowledge and task areas. The authors found that paraprofessionals worked with a broad range of stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
187
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(209 citation statements)
references
References 42 publications
8
187
1
3
Order By: Relevance
“…In contrast this result is contrary to that of Carter et al (2009) who reported from their findings that in general TAs reported feeling just adequately prepared to assume the tasks they were frequently assigned. From their results, Carter et al (2009) were unable to ascertain whether TAs felt more competent in tasks they regularly performed or whether TAs were assigned tasks they were more prepared to perform. This study found that the majority of TAs (66.9%) felt they were "very prepared" or "moderately prepared" to perform the task assigned to them.…”
Section: Preparednesscontrasting
confidence: 56%
See 3 more Smart Citations
“…In contrast this result is contrary to that of Carter et al (2009) who reported from their findings that in general TAs reported feeling just adequately prepared to assume the tasks they were frequently assigned. From their results, Carter et al (2009) were unable to ascertain whether TAs felt more competent in tasks they regularly performed or whether TAs were assigned tasks they were more prepared to perform. This study found that the majority of TAs (66.9%) felt they were "very prepared" or "moderately prepared" to perform the task assigned to them.…”
Section: Preparednesscontrasting
confidence: 56%
“…This study found that the majority of TAs (66.9%) felt they were "very prepared" or "moderately prepared" to perform the task assigned to them. Similar to Carter et al (2009) the results did not specify whether this was because TAs were assigned to tasks they were more prepared to perform or whether they were competent in tasks they regularly performed, however as the average time working as a TA was nearly 10 years (M = 9.9 years) it could be inferred that on-the-job experience provided the knowledge and skills to enable TAs to rate themselves as more than adequate in performing these tasks. Additionally eighteen of the participants (11%) indicated they had also worked as a qualified teacher, implying they have a high level of preparedness to perform their role.…”
Section: Preparednesssupporting
confidence: 51%
See 2 more Smart Citations
“…• Les AE représentent le personnel auxiliaire le moins qualifié auprès d'élèves dont les difficultés d'adaptation sont les plus complexes (Carter, O'Rourke, Sisco et Pelsue, 2009;Chopra, Sandoval-Lucero, Aragon, Bernal, Berg De Balderas et Carroll, 2004;Jones et Bender, 1993;Katsiyannis, Hodge et Lanford, 2000). • Dans certains milieux scolaires, les méthodes d'intervention des AE tendent à faire plus de tort que de bien aux élèves concernés (Angelides, Constantinou et Leigh, 2009;Hardy, 2004;Riggs et Mueller, 2001;Rueda et Deneve, 1999).…”
Section: Tableau 2 Exemples De Responsabilités Ne Relevant Pas Des Funclassified